Ремісниче виробництво давньоруського поселення Автуничі - Петраускас, А.В. (Археологія, 1998)
У роботі запропоновано спробу охарактеризувати і виділити особливості різних видів сільських ремесел за матеріалами пам'ятки, дослідженої поблизу с. Автуничі Чернігівської обл. Ремесло — одна из важнейших отраслей феодальной экономики. Оно обеспечивало население необходимыми средствами производства и орудиями труда, бытовыми предметами, украшениями, одеждой и т. д.
В работе рассматриваются остатки ремесленного производства, обнаруженные в ходе исследований поселений конца X — рубежа XII—XIII вв. возле с. Автуничи Черниговской обл. Отмечены особенности уровня развития различных видов ремесел, отличия от городского производства. Handicraft is one of the most important branches of feudal economic structure. It provided the population with the necessary means of production and implements of labour, house utensils, adornments, clothes and so on.
Remnants of goods of handicraft work which were found in the course of examination of the settlement dated the late 10th and 12th-13th centuries near village Avtunichi, the Chemygiv region are described in the paper. Certain peculiarities in the level of development of different kinds of handicrafts and the features distinguishing them from urban handicraft production are presented.